Measuring the Halalness of Medical Drugs Containing Alcohol - Nurjannah Nurjannah; Syamsul Bakhri; Irma Nur Afiah (International Journal of Halal System and Sustainability, 2021)
Indonesia is a country that has the largest number of Muslims in the world, where around 80% of the population is Muslim. Every Muslim is instructed only to consume foods and drinks that are halal and beneficial to the body, including medical drugs, which are the topic of discussion in this paper. Medical drugs are drugs derived from substances or chemicals and chemicals, which are useful for diagnosing, preventing, reducing, eliminating, and curing diseases or symptoms of diseases, injuries, or physical and spiritual disorders in humans or animals, including beautifying the body or human body parts. The need for halal medicine is still an interesting issue to continue to be discussed, considering a large number of requests and many medicines that contain substances Islam prohibits. This paper aims to see whether it is halal or haram to consume medical drugs that contain alcohol. The approach discussed in this paper uses the basis of the Al-Qur'an, Hadith, and Fatwas of the Indonesian Ulema Council (MUI). The halalness of medical drugs includes three factors: the materials used, the production process, and product storage. Based on the MUI fatwa, drinks (including medical syrup types) containing more than 1% alcohol are haram to consume, except in emergencies. The purpose of an emergency is a situation in which there are no other types of medical drugs available in the area except for medical drugs that contain alcohol. In this regard, a polemic has emerged, namely, whether there is currently a situation and condition called an emergency, considering that there are many experts in the pharmacy field and technological sophistication. The result of the discussion of this paper is that if there is a medical drug that does not contain alcohol, then a medical drug that contains alcohol is haram for consumption by Muslims.